Land administration and the right of access to land: an analysis of the concept of temporary occupation license under Malaysian land law - Kadouf, Hunud Abia (LexisNexis, 2011)
Modern problems such as globalisation, population growth, urban expansions and the ever increasing demand for land require that sustainable management of scarce natural resources, such as land becomes a necessity. LAck of good governance and proper land administration is one of the many problems endemic to ddeveloping countries. This has adverse effects not only to the proper economic and agricultural development of these countries but also in distorting equitable distribution of land thus affecting social equilibrium of these societies. Most of the countries have devised ways and means to ensure that, at least, the majority of their population have proper access to land. Some of these devices may prove successful while others have yet to test of their usefulness.